2019
DOI: 10.3389/fgene.2019.00748
|View full text |Cite
|
Sign up to set email alerts
|

Casein Gene Cluster in Camelids: Comparative Genome Analysis and New Findings on Haplotype Variability and Physical Mapping

Abstract: The structure of casein genes has been fully understood in llamas, whereas in other camelids, this information is still incomplete. In fact, structure and polymorphisms have been identified in three ( CSN1S1 , αs1-CN; CSN2 , β-CN; CSN3 , κ-CN) out of four casein genes, whereas controversial information is available for the CSN1S2 (αs2-CN) in terms of structure and genetic diversity. Data from the genome analysis, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 85 publications
4
28
0
Order By: Relevance
“…All these caseins are encoded by autosomal genes CSN1S1, CSN2 , CSN1S2 , and CSN3 , respectively in closely linked DNA clusters ( Pauciullo et al, 2019 ). The genomic cluster of the casein gene spans between 250 and 350 kb in different mammalian species ( Ryskaliyeva, 2018 ), and in buffalo entire CSN gene covers a region of 250kb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these caseins are encoded by autosomal genes CSN1S1, CSN2 , CSN1S2 , and CSN3 , respectively in closely linked DNA clusters ( Pauciullo et al, 2019 ). The genomic cluster of the casein gene spans between 250 and 350 kb in different mammalian species ( Ryskaliyeva, 2018 ), and in buffalo entire CSN gene covers a region of 250kb.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the genomic sequences were analyzed in TFBIND software 8 by using the transcription factor database TRANSFAC R.3.4 weight matrix to find the transcription factor binding sites ( Tsunoda and Takagi, 1999 ). According described previously, four potential transcription factor binding sites (GATA, TATA, STAT, and OCT1) ( Hennighausen and Robinson, 1998 ; Robinson et al, 1998 ; Rosen et al, 1999 ; Wheeler et al, 2001 ; Wyszomierski and Rosen, 2001 ; Yamashita et al, 2001 ; Chughtai et al, 2002 ; Pauciullo et al, 2019 ) and one repressor site (YY1) ( Helman et al, 1998 ; Tomic et al, 1999 ) in casein genes of Mediterranean and swamp buffalo in 100bp upstream regions of the potential signal site were calculated ( Wyszomierski and Rosen, 2001 ). The significant difference for the distribution of putative transcription factor binding and repressor sites in Mediterranean and swamp buffalo was statistically evaluated by using a t -test with a P- value of < 0.05 as statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is a relatively rare event. In fact, it is well-known that many recombination events characterise the casein cluster (Caroli et al 2009;Pauciullo et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Although many retroposons are common for the ruminants and non-ruminant species and, thus, are likely of ancestral origin, every species has a definite number of short interspersed nuclear elements, which contributes to make each genome specific for each species (Ramunno et al, 2004 ; Cosenza et al, 2005 ; Pauciullo et al, 2013 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of interspersed repeats within or near genes has been studied in ruminants as well as in camelid casein genes (Groenen et al, 1993 , Ramunno et al, 2004 , Cosenza et al, 2009b , Pauciullo et al, 2013 , 2014 , 2019 ). It has not been observed that insertions within or near promoters or 3′ UTR can alter gene expression.…”
Section: Discussionmentioning
confidence: 99%